Current insights into the microbial degradation for pyrethroids: strain safety, biochemical pathway, and genetic engineering. (September 2021) - Zhao, Tianye; Hu, Kaidi; Li, Jianlong; Zhu, Yuanting; Liu, Aiping; Yao, Kai; Liu, Shuliang
Abstract: As a biologically inspired insecticide, pyrethroids (PYRs) exert evident toxic side effects on non-target organisms. PYRs and their general toxic intermediate 3-phenoxybenzoic acid (3-PBA) have shown high detection rates/levels in human beings recently, for which diet was identified as the major exposure route. Microbial mineralization has emerged as a versatile strategy in addressing such escalating concern. Herein, PYRs and 3-PBA biodegradation with regards to strain safety, application and surfactant were summarized. Numerous PYRs-degrading microbes have been reported yet with a minority focused on 3-PBA. Most isolates were from contaminated sites while several microbial food cultures (MFCs) have been investigated. MFCs such as Bacillus spp. and Aspergillus spp. that dominate in PYRs-degrading microbial pools are applicable candidates for agricultural by-products detoxification during the postharvest process. Subsequently, we discussed committed degradation steps, wherein hydrolase responsible for PYRs ester linkage cleavage and oxygenase for 3-PBA diphenyl ether bond rupture play vital roles. Finally, comprehensive information of the key enzyme genes is outlined along with methodologies concerning gene cloning. Cytochrome P450 monooxygenases (CYP) is competent for diphenyl ether scission. Newly-developed omics has become a feasible gene and enzyme mining technology. To achieve PYRs mineralization in feed and food commodities, the screening of MFCs rich in related enzymes and the construction of MFCs-derived genetically modified microbes (GMMs) exhibit great potential considering the safety issues. Graphical abstract: Image 1 Highlights: Pyrethroids and their metabolite 3-phenoxybenzoic acid are of great concern. Application of microbial food cultures in feed and food during postharvest process. Cleavage of pyrethroids ester linkage and diphenyl ether bond are discussed. Key enzyme genes are outlined along with genetic engineering methodologies. Genetically modified microbes exhibit mineralization potential for pyrethroids.